Voisinages fragiles Les relations interconfessionnelles dans le Sud-Est européen et la Méditerranée orientale 1854-1923 : contraintes locales et enjeux internationaux - Anastassiadis, Anastassios (Mondes méditerranéens et balkaniques (MMB), 2013)
Voisinages fragiles is the first product of an on-going collective effort participating in the wider effort of writing a connected history of the Eastern Mediterranean in the 19th and 20th centuries. This history breaks away from the arbitrary geo-disciplinary yoke of area studies which forces specialists of the Ottoman Empire, the Middle East and the Balkans to work in separate clusters. This history also challenges the perception of this space in terms of essentialist and monolithic religious, political and identity frameworks. It underlines the heuristic value of studying interactions to the fullest extent possible. Our multi-scalar analytical approach (local, regional, national, imperial, global) brings to life a first panorama of the wide variety of contacts, the multitude of individual and institutional strategies, the complex relationship between religions, identities and politics.